My name is Yoon - Recorvits, Helen. (Frances Foster Books, 2003)
Disliking her name as written in English, Korean-born Yoon, or "shining wisdom," refers to herself as "cat," "bird," and "cupcake," as a way to feel more comfortable in her new school and new country.